Immunopathogenesis of cow’s milk allergy - Ariyanto Harsono (Indonesian Pediatric Society, 2003)
Given the public’s increasing awareness of cow’smilk allergy and their frequent misperception thatvarious illness is caused by cow’s milk-induced aller-gic reactions, the physician must retain some skepti-cism throughout the evaluation and rely on objectivemeasures to arrive at the final diagnosis. Over diag-nosis of cow’s milk allergy has led to malnutrition,eating disorders, and psychosocial problems, as wellas family disruption, whereas under diagnosis leavesthe patient suffering unnecessarily and may result ingrowth failure and permanent physical impairments.The following discussion provides an immunologicalbasis of cow’s milk allergy in an attempt to improveour understanding in clinical manifestations, diagno-sis and management of the disease.